Maasi, the Living Husband and Ayadroh, the Spiritual Consort of the Tribe of Arunachal Pradesh - Vokendro, Haobijam; Bagang, Apo (Tri-Chandra Journal of Anthropology, 2025)
The Sartang tribe of Arunachal Pradesh is a less known minor tribe formerly clubbed under the category of Monpa. The people observes an annual calendar ritual to ward off evil spirits from harm and dismay of the people and their village. A boy called Maasi is selected by a priest from among a group of teenage boys who is considered to be the spouse of a female evil spirit. The data was collected by interviewing key informants. The researcher also employed observation of the ritual event and recording using research tools such as audio and camera. The analysis of the data was done using ethnographic methods. The paper describes the power, role and different stages of the Maasi in the annual calendar ritual. The rites and ceremonies practised by the Sartang people are believed to atone for one’s misdeeds, bring good fortune and longevity and avoid malicious gossip to keep harmonious relationships in the community.